PATH-24. ACCURATE IDENTIFICATION OF GLIAL MALIGNANCIES FROM PERIPHERAL BLOOD. (14th November 2022) - Anichini, Giulio; Fulmali, Pooja; O'Neill, Kevin; Datta, Vineet; Crook, Timothy; Syed, Nelofer
Abstract: Symptomatic presentation of patients with intra-cranial malignancy is frequently non-specific and differentiating such patients from those with benign conditions is challenging. Accordingly, GBM presents as a medical emergency more frequently than any other common cancer, implying that effective strategies for rapid and simple diagnostic stratification of such patients are urgently required. Here we describe the detection of glial malignancies based on the enrichment and identification of Circulating Glial Cells (CGCs) in peripheral blood. The first case controlled study included blood from 189 participants split into discrete training and test sets (145 GBM, 44 benign CNS conditions). The second case controlled study included 40 cases of glial malignancies, 22 benign CNS conditions, 24 solid tumors with brain metastases, and 500 healthy individuals with no prior diagnosis of cancer and no current suspicion of cancer. A third prospective study was also carried out in 68 individuals with radiologically evident intracranial space-occupying lesion suspected of glial malignancies. Blood specimens were blindly evaluated for detection of CGCs through TruBlood assay to determine clinical sensitivity and specificity. 98% sensitivity and specificity was observed in detecting glial malignancies and differentiating them from benign CNS conditions in both case controlled studies. We detected and differentiated glial malignancies from benign CNS, healthy samples, and brain metastases. In the prospective study, 56 were positive for CGS, and 12 were negative for CGCs. All CGC positive specimens were confirmed glial malignancies and all CGC negative specimens benign CNS conditions. We present a non-invasive approach to the diagnostic stratification of patients presenting with suspicious but non-specific neurocognitive symptoms and hence early detection of glial malignancies. Moreover, immunocytochemistry facilitates the differentiation of GBM from metastatic intra-cranial epithelial cancers.